2010
DOI: 10.1002/cphc.200900894
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Phytochromes

Abstract: Photosensory proteins enable living things to detect the quantity and quality of their light environment and to transduce that physical signal into biochemical outputs which entrain their metabolism with the ambient light environment. Phytochromes, which photoconvert between red-absorbing Pr and far-red-absorbing Pfr states, have been the most extensively studied of these interesting proteins. Critical regulators of a number of key adaptive processes in higher plants, including photomorphogenesis and shade avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
423
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(433 citation statements)
references
References 82 publications
(215 reference statements)
2
423
0
3
Order By: Relevance
“…Similarly, it has been suggested that two-Cys CBCRs can sense the cellular redox potential via oxidation of the second Cys, which arrests the photocycle (21). There also are many examples of tandem CBCR sensors containing multiple GAF domains that perceive light of various colors (1,2,14,19,23,24). CBCRs thus are exceptionally sophisticated photosensors, able to integrate light with various physiological cues and to provide complete coverage of the entire visible spectrum with a single chromophore precursor and a small, soluble protein sensor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it has been suggested that two-Cys CBCRs can sense the cellular redox potential via oxidation of the second Cys, which arrests the photocycle (21). There also are many examples of tandem CBCR sensors containing multiple GAF domains that perceive light of various colors (1,2,14,19,23,24). CBCRs thus are exceptionally sophisticated photosensors, able to integrate light with various physiological cues and to provide complete coverage of the entire visible spectrum with a single chromophore precursor and a small, soluble protein sensor.…”
Section: Discussionmentioning
confidence: 99%
“…S1B). * Cyanobacteriochromes (CBCRs) are widespread cyanobacterial photosensors with phytochrome-related GAF domains (1,2,13,14). Although CBCRs also convert between two photostates via bilin photoisomerization at C15, they exhibit much more spectral diversity, with peak absorptions ranging from 330 to 680 nm and hence spanning the entire visible spectrum and near UV (13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(SynCph2) (10) and several other cyanobacterial phytochromes (11). Finally, the cyanobacteriochromes (CBCRs, Group III) utilize a single, bilin-binding GAF domain (11,12). CBCRs cover a broad range of the visible/near UV spectrum but are restricted to cyanobacteria.…”
mentioning
confidence: 99%
“…Protonemata and gametophores of Physcomitrella patens subsp. patens were grown on solid Knop's medium or cultured in liquid PPNH 4 . Spores were germinated on solid Knop's medium supplemented with 10 mM CaCl 2 and overlaid with cellophane.…”
Section: Methodsmentioning
confidence: 99%